Optimizing Craft Business Performance Through Strategic Mapping with SWOT and BMC - Nur Permatasari, Maynda Cessaria; Yulianti, Ida (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to design an appropriate business planning strategy for Cacylflow to overcome business challenges, including unstable sales, limited human resources, and suboptimal marketing, as well as to identify effective solutions for increasing sales turnover. Design/Methodology/Approach – This study employs a descriptive qualitative approach. Data were collected through observation, interviews, and literature studies. The analysis was conducted by evaluating internal and external business conditions using SWOT analysis and Business Model Canvas (BMC), supported by investment feasibility analysis using Net Present Value (NPV), Profitability Index (PI), and Payback Period methods. Findings – The results indicate that the proposed strategies for Cacylflow include product diversification, marketplace expansion, service improvement through greeting board rental and workshops, workforce development through collaboration with women’s organizations (PKK), and strengthening online and offline promotional activities. Furthermore, the investment feasibility analysis shows that the Cacylflow business is financially feasible for development. Originality/Value This study presents a practical business planning framework for pipe-cleaner–based handicraft enterprises, a niche sector rarely examined academically. By integrating SWOT, BMC, and investment feasibility analysis, it offers actionable and context-specific strategies that support growth, innovation, and long-term viability.